PENINGKATAN KINERJA GURU DALAM PEMBELAJARAN TEMATIK MELALUI SUPERVISI AKADEMIK - Edi Priyanto (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
This study aims to improve teacher performance in implementing thematic learning through academic supervision at SD Negeri Batuagung 02, Balapulang District, Tegal Regency. The research approach used was School Action Research (SAR). The research subjects were 4 teachers in class IA, IB, IVA, and IVB. Data collection techniques with observation and interview sheets. The data analysis technique used comparative descriptive analysis. The results of school action research can be concluded that academic supervision can improve teacher performance in implementing learning at SD Negeri Batuagung 02, Balapulang District, Tegal Regency. The resulting impact of increasing teacher performance concerns aspects of the implementation of learning. From the learning aspect, after being given action by the principal through qualitative academic supervision, the implementation of learning increased from the initial conditions to the first cycle of 0.60 and from the first cycle to the second cycle of 0.69. The learning outcomes of class IA students in cycle I increased by 4.53 compared to the initial condition, in cycle II increased by 5.38 compared to cycle I. The learning outcomes of class IB students in cycle I increased by 4.13 compared to the initial condition, in cycle II increased by 4.68 Compared to cycle I. The learning outcomes of class IV A students in the first cycle increased 1.94 compared to the initial conditions, in the second cycle increased 5.92. The learning outcomes of class IV B students in cycle I increased by 4.53 compared to the initial conditions, in cycle II increased by 5.38 compared to cycle I.